THE EFFECTIVENESS OF MEET APPLICATION AS ONE OF ONLINE LEARNING MEDIA DURING PANDEMIC IN STIKES BULELENG’S PHARMACY STUDENTS - Devy Marleni; Windi Ridayanti (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Covid-19 pandemic that has spread over 2 past years forced education world to look for other alternatives in doing learning process. It is because there is limited on activities that involve many people. All students, both students and college students, are required to study at home using online media. Teaching was changed from face to face to online system. All online-based teaching does from elementary school to high school and university levels. Sekolah Tinggi Ilmu kesehatan Buleleng (Setikes Buleleng) is one of school that implements online learning using Meet application. Meet is one of the online learning media used by students in attending lectures during pandemic. Online learning is really needs to be considered so that students understand when learning takes place. The purpose of this study is to find out and understand the effectiveness of online learning uses Meet at Stikes Buleleng. This study uses a qualitative research approach. In this study, the researcher uses approach based on the post-positivism paradigm. The data collected by doing interviews to the students. Based on the results of the study, it is found that online learning using Meet is effective. Online learning received a very good response from students because learning is more flexible when using it. With online learning, students are more enjoy, relax and encourage students to be more active in their studies. The existence of features in Meet makes learning more interesting so that students do not feel bored in attending lectures.